Expressions of circadian clock genes represent disease activities of RA patients treated with biological DMARDs. Issue 2 (3rd March 2020) - Kaneshiro, Kenta; Yoshida, Kohsuke; Morii, Kanta; Oketani, Yuto; Uchida, Koto; Yaekura, Arisa; Okumura, Ikumi; Hashimoto, Teppei; Kawasaki, Yoshiko; Shibanuma, Nao; Sakai, Yoshitada; Hashiramoto, Akira
Abstract: Objectives: Rheumatoid Arthritis (RA) is the autoimmune disease representing the circadian variations of symptoms such as morning stiffness of joints or increased production of cytokines around midnight. Clock genes have been reported to affect on the pathogenesis of RA, however, the detailed relation between clock genes and disease activities of RA has remained unclear. Methods: In this study, 15 RA patients treated with biological disease modifying anti-rheumatic drugs (bDMARDs) were enrolled (TNF inhibitor, 5; IL-6 inhibitor, 5; CTLA4-IgG, 5). Blood samples were collected from RA patients before treatment and at the study end-point fulfilling DAS28-ESR < 3.2. Total RNA was extracted from leukocytes to examine the expressions of the clock genes. We then evaluated the correlation of the clock gene expression with disease activity and the diagnostic values of the clock genes. Results: The expressions of the clock genes were significantly modulated by bDMARDs treatments. Disease activities were significantly correlated with the clock genes expressions, and disease remission/low disease activity could be distinguished from moderate/high disease activity due to the sensitivities, the specificities and the areas under the curves of that. Conclusion: The expressions of the clock genes in leukocytes could be useful as novel biomarkers predicting disease activities and therapeutic efficacies for bDMARDs in RA treatments.